Controlling Activity of Heterogeneous Cu Single‐Atom Catalysts by Fine‐Tuning the Redox Properties of CeO2‐TiO2 Supports. Issue 8 (3rd April 2023) - Abdel‐Mageed, Ali M.; Cisneros, Sebastian; Mosrati, Jawaher; Atia, Hanan; Vuong, Thanh Huyen; Rockstroh, Nils; Wohlrab, Sebastian; Brückner, Angelika; Rabeah, Jabor
Abstract: Understanding and enhancing the activity of heterogeneous single‐atom catalysts (SACs) are indispensable aspects to use them in industrial applications. Among these, low‐temperature CO oxidation is considered as a model reaction for testing a wide‐range of oxidation catalysts, and as an essential process for the exhaust aftertreatment in modern combustion engines. This study demonstrates that the activity of heterogeneous Cu/CeO2 −TiO2 SAC catalysts can be fine‐tuned by controlling the Ce/Ti ratio in CeO2 −TiO2 supports, with the highest catalytic activity achieved for a Ce/Ti molar ratio of 0.18. Based on DRIFT, EEL, and EPR spectroscopies, together with high‐resolution electron microscopy and H2 ‐TPR measurements, it is inferred that the optimized Ce/Ti ratio correlates with i) highest dispersion of separate CeO2 particles on TiO2 surface, ii) more facile reduction of Ce 4+ to Ce 3+, and iii) enhanced formation of −Cu 2+ −O−Ce 4+ −⇆−Cu + −□−Ce 3+ − redox shuttles, which play a dual role for CO adsorption and O2 ‐activation. These results extend the understanding of heterogeneous metal single‐atom catalysts and constitute a robust approach for the rational control of their catalytic performance in technically relevant applications. Abstract : Optimizing the activity of heterogeneous single‐atom catalysts (SACs) is indispensable to use them in industrial applications. This study demonstrates that the activity of heterogeneous Cu/CeO2 −TiO2 SAC catalysts can be fine‐tuned by controlling the Ce/Ti ratio in CeO2 −TiO2 supports. A multitude of characterizations including operando / in situ spectroscopic methods reveal a magic ratio of Ce/Ti around which catalytic activity culminates.